The joy of discipleship : reflections from Pope Francis on walking with Christ - Francis, Pope, 1936-2025; Campbell, James P. (Theologian) (Chicago : Loyola Press, 2016)
In The Joy of Discipleship, Pope Francis reminds us that joy should be one of the defining characteristics of any person who has truly encountered Jesus. This skillfully curated collection of homilies, speeches, and other documents from Pope Francis, compiled and edited by James P. Campbell, offers a fresh perspective on why Christian disciples should be so joyful in the first place and how that joy might manifest itself in our individual daily lives.
The extraordinary year of mercy -- The essential thing is mercy -- God's patience toward us -- Jesus is risen! We have seen him! -- Our joy is Jesus Christ -- The presence of God in the family -- Love is the measurement of faith -- Jesus has shared our journey -- The Holy Spirit is the soul of mission -- The church, God's great family -- Mary, model of union with Christ -- The saints, anchored in hope.
Includes bibliographical references (pages 93-107).
Keywords: Christian life; Joy -- Religious aspects -- Christianity